Pengetahuan dan Religiusitas Terhadap Niat Nasabah Menggunakan Produk Pembiayaan Pada Bank Wakaf Mikro - Rizki Yati, Heliana; Purwanto; Nur Alfianto, Achmad (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to analyze the impact of knowledge and religiosity on customers' intentions to use financing products at BWM. This type of research is quantitative research using data collection techniques through questionnaires. The population of this research is BWM Syubbanul Wathon Maslahah Magelang customers. The research sample is BWM Syubbanul Wathon Maslahah Magelang customers using 136 customers. The data analysis technique uses the multivariate statistical method of Structural Equation Modeling (SEM) using Particle Least Square (PLS) and is calculated through the Warp PLS 6.0 computer program. The sampling technique used purposive sampling. The results of this study are that there is a positive influence of knowledge and religiosity on financing intentions at BWM.